2008
DOI: 10.25011/cim.v31i1.3136
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 and PCNA expression in prostate cancer and benign prostatic hyperplasia

Abstract: Clin Invest Med 2008; 31 (1): E8-E15. AbstractObjective: Ki-67 is a proliferation-associated nuclear antigen and is expressed in all cycling cells except for resting cells in the G0-phase. PCNA is an acidic nuclear protein and has been recognized as a histologic marker for the G1/ S phase in the cell cycle. Ki-67and PCNA labeling indices are considered to reflect cell proliferation, particularly, growth fraction. The purpose of this study is to investigate the expression levels of Ki-67 and PCNA in prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 15 publications
11
69
3
1
Order By: Relevance
“…Since survivin was reported to be a downstream regulator in the ID1/PI3K/Akt/NF-κB/survivin signaling pathway for endothelial progenitor cell proliferation, and CRC tumor growth and malignant metastasis (25,26), the fact that ID1 knockdown induced a decrease in survivin expression, may indicate that activation of survivin is a consequence of the expression of ID1 in CRC cell lines. It has been suggested that PCNA is a proliferation marker of tumors and is critical for DNA synthesis (27). We showed that ID1 knockdown decreased PCNA expression at both the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 57%
“…Since survivin was reported to be a downstream regulator in the ID1/PI3K/Akt/NF-κB/survivin signaling pathway for endothelial progenitor cell proliferation, and CRC tumor growth and malignant metastasis (25,26), the fact that ID1 knockdown induced a decrease in survivin expression, may indicate that activation of survivin is a consequence of the expression of ID1 in CRC cell lines. It has been suggested that PCNA is a proliferation marker of tumors and is critical for DNA synthesis (27). We showed that ID1 knockdown decreased PCNA expression at both the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 57%
“…PCNA expression is significantly elevated in patients with BPH or prostate cancer, and the extent of cell proliferation is related to the clinical grade of prostate cancer. 37) Animals with experimentally induced BPH also have significantly increased prostatic PCNA expression. 38,39) We found that rats with BPH that were given QI treatment had significantly reduced expression of PCNA and cyclin D1, as well as fewer PCNA-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA gene deregulation and post-translational modulation are hallmarks of malignant cells. Tumor cells, regardless of their origins, express higher levels of PCNA (Celis and Olsen, 1994;Kallakury et al, 1999;Kimos et al, 2004;Malkas et al, 2006;Miyamoto et al, 2006;Naryzhny and Lee, 2007;Eltz et al, 2008;Naryzhny, 2008;Stuart-Harris et al, 2008;Zhong et al, 2008;Stoimenov and Helleday, 2009). Expression levels of PCNA correlate positively with other pathological indices in prostate cancer (Mulligan et al, 1997) and can serve as an independent prognosis marker (Miyamoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%